Teacher Readiness in Implementation of Merdeka Curriculum on Preparation of IPAS Teaching Devices My Indonesia Rich in Culture and History Material - Hanaa Amatul Faatih; Akhmad Junaedi; Sigit Yulianto; Tri Astuti (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
The Merdeka Curriculum is the newest curriculum currently being implemented in Indonesia. The changes contained in the Merdeka Curriculum is in the composition of teaching devices and a new subject, namely Natural and Social Sciences (IPAS). Currently, many schools are adapting on implementing the Merdeka Curriculum, so it is necessary to have studies on analysis in the preparation of teaching devices, especially in natural and social science subjects so that implementation is in accordance with the Merdeka Curriculum. This study focused on IPAS subjects, especially on rich culture of my Indonesia material, to find out how teachers instill character values through culture and history to students. This study uses a descriptive qualitative research method with data collection techniques through interviews with teachers readiness and documentation of teaching devices. The result of this research will describe the teacher readiness analysis as well as the supporting factors and inhibiting factors faced by teachers in preparing the teaching devices for IPAS subjects in even semester at one of the leading schools in Tegal City, namely SDIT Usamah.